PENGARUH PENGGUNAAN MEDIA MANIPULATIF TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA SD - Adela, Yara (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of the research is to analyse the effect of the use manipulative media toward the students’ study result in SDN 30 South of Pontianak on class 4. The methode that has been used was experimen method with forms of quasi experimental research design in the stake nonequivalent control group design. Research population of the entire 4A and 4B consists of 44 students in SDN 30 South of Pontianak. The research sampel is all of population that is class 4A (experiment class) and class 4B (control). Based on the result of data analysis the median of post test in experiment class was 83,73, meanwhile the control class was 72,42. The hypothesis test result using t-test (Polled Variance) with dk 42 on 5% significant level as known as table t= 1,682 obtained count (table t =1,682 ). Then Ha accepted and Ho rejected it could be conclude that there is an influence of the use of manipulative media toward students’ study result on the simple fraction in SDN 30 South of Pontianak on class 4. The result of the calculations on the effect size in experiment class was 0,83 (high criteria). It means that the use of manipulative gave high influence (effect) toward students’ study result on simple fractions in SDN 30 South of Pontianak. Keyword : Influence, Manipulative Media, Study Result